KGB struggle against emigree with propaganda and ideological means in XX century 9 decade. - Burinskaitė, Kristina (Genocidas ir rezistencija, 2008)
One of the most important tasks of the KGB’s intelligence and ideological counter-intelligence units was to weaken the diaspora’s anti-Soviet activities, to prevent it from raising the issue of Lithuania’s occupation at the international level and from supporting the different-minded people in Lithuania. It was also important for the Soviet government to change the diaspora’s attitude towards Soviet Lithuania and to break its policy of non-recognition.
Keywords: KGB; emigree; propaganda; intelligence; KGB methods; press